2012
DOI: 10.1002/hed.22008
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment levels of peripheral neutrophils and lymphocytes as independent prognostic factors in patients with nasopharyngeal carcinoma

Abstract: Pretreatment NLR and percentages of lymphocyte and neutrophil are independent prognostic factors and may serve as clinically convenient and useful biomarkers for survival of patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
202
7
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(222 citation statements)
references
References 39 publications
11
202
7
2
Order By: Relevance
“…Neutrophilia may inhibit the immune system by suppressing lymphocytes, activated T cells and natural killer cells (3,17). The prognostic role of the NLR has been evaluated in >60 studies on a number of solid tumors (7)(8)(9)(10)(11)(12)(13)(14)16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophilia may inhibit the immune system by suppressing lymphocytes, activated T cells and natural killer cells (3,17). The prognostic role of the NLR has been evaluated in >60 studies on a number of solid tumors (7)(8)(9)(10)(11)(12)(13)(14)16,18).…”
Section: Discussionmentioning
confidence: 99%
“…NLR was reported to be an independent prognostic factor for patients with various types of cancer. An increase in NLR has been shown to be associated with adverse overall survival (OS) in several solid tumors (3); a high NLR was associated with adverse outcomes of nasopharyngeal carcinoma, castration-resistant metastatic prostate carcinoma, breast cancer, non-small-cell lung cancer (NSCLC), local and advanced esophageal squamous carcinoma and renal cell carcinoma (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies exist on the prognostic role of peripheral leukocytes and differential counts of neutrophils and monocytes in NPC. He et al (21) and Sun et al (22) investigated the association of neutrophils and lymphocytes with PFS and OS in NPC; however, the authors did not evaluate the endpoints for distant metastasis and locoregional recurrence. The prognostic roles of leukocyte and monocyte count were not addressed in above two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that complete blood count (CBC) parameters associated with systemic inflammation, including leukocytes and their differential counts, are clearly correlated with prognosis in patients with a variety of neoplasms (17)(18)(19)(20), including NPC (21,22). However, previous studies on NPC usually utilize limited endpoints, including overall survival (OS) and progression-free survival (PFS) (21,22). The prognostic value of peripheral leukocytes and differential counts of neutrophils and monocytes in patients with NPC has not been sufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In patients with nasopharyngeal carcinoma, NLR was significantly associated with overall survival and progressionfree survival. [16] Hemoglobin, NLR and platelet count in patients with nasopharyngeal carcinoma are found useful to predict long-term mortality. [17] Another study suggests that high pretreatment NLR is significantly associated with poor disease-specific survival in oral cancer patients undergoing preoperative chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%